The batting backlift technique in cricket - Noorbhai, Mohammed Habib (MRC/UCT RU for Exercise and Sport Medicine, 2017)
The batting technique in cricket consists of various elements such as the grip, stance, backlift, downswing, impact with the ball and follow through. Whilst there has been an extensive amount of research into these batting elements, there is little research specifically on the backlift technique. Therefore, we aimed to investigate and provide a scientific understanding of the batting backlift technique (BBT) in cricket. We aimed to investigate the BBT of the most successful batsmen (n = 65) in the last 120 years as well as players in the Indian Premier League (IPL) (n = 30). It was found that these batsmen did not conform to the current cricket coaching method that advocates a straight batting backlift technique (SBBT). Instead, 77% of successful batsmen and 90% of IPL batsmen employed a lateral batting backlift technique (LBBT) in which they lifted their bats in the direction of second slip or beyond with the bat face towards the off-side. Using this technique, both the toe of the bat and face of the bat points directly towards the off-side (usually between slips and point). The number of players using the LBBT was significantly greater than those using the SBBT (χ2 = 19.2, df = 1, p < 0.001). Given these findings, we were curious to determine whether this finding was similar at other levels of cricket. The second study therefore employed biomechanical and video analyses to evaluate the BBT of current semi-professional, professional and international cricketers (n = 155) from South Africa and the United Kingdom. The backlift of these batsmen was then compared to their career statistics. It was found that a LBBT is more prevalent at the highest levels of the professional game and a likely contributor factor for successful batting at the highest level (p≤0.05). The LBBT was also found to positively affect other components of the batting technique such as the stance and scoring areas. We then proceeded to investigate the BBT amongst the lower levels of cricket (junior and adolescent cricketers). The third study consists of an intervention study that employed a biomechanical analysis of coached and uncoached cricketers (n = 80). It was found that more than 70% of uncoached cricketers adopted a LBBT, whereas more than 70% of coached cricketers adopted the SBBT. Having found that the LBBT is a likely contributing factor for past and current successful batsmen, it was then important to understand what BBT the current cricket coaches are teaching at various proficiency levels. The fourth study explored the teachings of the BBT among international cricket coaches (n = 161) using a mixed methods approach through an online evaluation survey. This study was able to show that a majority of cricket coaches teach what is advocated in coaching manuals and mostly coach the SBBT as opposed to the LBBT at various levels of the game. In the fifth and sixth studies, this thesis further describes two innovative coaching tools that can improve and assist with the coaching of the LBBT. Firstly, a novel coaching cricket bat was investigated through a pilot and intervention study. In the pilot group, cricketers using the coaching bat scored approximately 1 more run per ball or an average of approximately three more runs in total when using the coaching bat than the normal bat (F = 6.70, df = 1, p = 0.012). In the intervention study, the experimental group scored double the total number of runs (an additional 16 runs) and an average of approximately 3 more runs per player in the post-match than in the pre-match, which showed a large effect (ES = 5.41) (t = 3.32, df = 5, p = 0.021). The coaching cricket bat might be used to coach young cricket players to hit the ball more effectively as well as how to adopt a more LBBT. Secondly, a mobile application was developed, which can be used by players, coaches and scientists to analyse and improve the BBT among cricketers at all levels. In summary, this thesis has shown that the LBBT is a likely contributing factor to successful batsmanship at all levels of cricket ability (junior cricketers, adolescent cricketers, semi-professional cricketers, professional cricketers, international cricketers and former elite/successful cricketers). Coaching a LBBT to young batsman may be challenging and therefore a coaching cricket bat has been developed and has shown to be a promising training aid for coaching the LBBT to young cricketers. A mobile application has also been designed and tested to assist in the coaching of the BBT in cricket. A way forward for further research in this area of cricket batting is documented at the end of the thesis.